2008
DOI: 10.11606/s1413-95962008000700019
|View full text |Cite
|
Sign up to set email alerts
|

Temperatura ambiente e concentrações séricas de cortisol em suínos em crescimento-terminação

Abstract: Thirty-six castrated males and females Landrace x Large-White pigs (74 to 149 days of age) were randomly allotted to two environmental conditions: high temperature in a climatic chamber (HT; 22.2 to 32.8 ºC) and comfort temperature in a conventional shed (CT; 17.6 to 26.6 ºC), with night-and-day variations. Blood samples were weekly collected from animals of both HT and CT conditions for determination of serum cortisol levels. Cortisol levels of both sexes were not different, and there was no interaction with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…The concentration of cortisol is 15% higher in barrows than in gilts [52]. HS-induced increases in the concentrations of catecholamines and glucocorticoids have been observed in many species [53,54]; the effect of HS on immune cells is suggested to be dependent upon these hormones [55][56][57]. Similarly, Rudolph et al [40], found that oxidative stress did not result in muscle injury in barrows, while…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of cortisol is 15% higher in barrows than in gilts [52]. HS-induced increases in the concentrations of catecholamines and glucocorticoids have been observed in many species [53,54]; the effect of HS on immune cells is suggested to be dependent upon these hormones [55][56][57]. Similarly, Rudolph et al [40], found that oxidative stress did not result in muscle injury in barrows, while…”
Section: Discussionmentioning
confidence: 99%
“…When animals are under heat stress, they tend to find ways to reduce it through physiological regulatory mechanisms, but in doing so the animals use energy that otherwise would be used for production, with a negative result for the production system (Smulders et al, 2006;Fagundes et al, 2008). Environmental factors influence the production level of animals, therefore this is an important subject of study, once less stressful environmental conditions may result in a maximum yield.…”
Section: Introductionmentioning
confidence: 99%
“…COSTA et al, 2007;CAMPOS et al ,2009). Entre as ferramentas usadas para mensurar o bem estar animal, destaca-se as medidas ambientais, os indicadores fisiológicos (temperatura corporal, níveis de cortisol, frequência respiratória, resposta imunológica) FAGUNDES et al,2008 ) e comportamentais (fugas, brigas, brincadeiras e vocalizações) (CANDIANI et al, 2008;KRANENDONK et al, 2006). A maioria dessas medidas é de difícil mensuração e inviável a avaliação por técnicos em granjas comerciais, sendo necessário um sistema automático para avaliação do bem estar.…”
Section: Resultsunclassified